ANALISIS EFEKTIVITAS PENGGUNAAN DANA DESA TERHADAP PENANGGULANGAN STUNTING DI KAMPUNG NAWARIPI DISTRIK WANIA KABUPATEN MIMIKA - Ria Mintje Ritiauw; Siske Tontong (CV. Adiba Aisha Amira, 2023)
This research aims to determine the effectiveness of using village funds in preventing stunting in Nawaripi Village, Wania District, Mimika Regency. The method used in this research is descriptive research method. The population in this study was pregnant women and children with a sample of 151 respondents. The sample used was a sample of respondents using the Slovin formula. Data collection techniques through questionnaires and documentation. The data analysis technique used in this research is a correlative descriptive statistical analysis technique in the form of a mean test (average), using the effectiveness formula. The research results show that the use of Village Funds to overcome stunting in Nawaripi Village is quite effective